Sea Ice Examination for Ice Class Ships visiting Horseshoe Island, Antarctica, Using MODIS in 2000-2022 - Yirmibeşoğlu, Sinan; Özsoy, Burcu (Transactions on Maritime Science, 2024)
Sea ice has a significant impact on numerous areas, ranging from the reflection of the sun rays back on the albedo scale, to spurring intense phytoplankton blooms that help maintain the marine ecosystem and making the navigation of some maritime routes challenging. The formation of sea ice in the Southern Ocean affects maritime logistics and scientific operations on Antarctica, especially on the Antarctic Peninsula, which hosts half of the scientific stations. Ships needed to supply British and Turkish scientific bases on Horseshoe Island in the southernmost part of the Antarctic Peninsula are in high demand. Therefore, the analysis of the oldest trends of sea ice that affect maritime operations is crucial. The goal of the study was to examine the formation of sea ice, and especially ice-free days, by using images collected between 2000 and 2022 by over 8000 NASA’s Terra/MODIS Moderate Resolution Imaging Spectroradiometer instruments (MODIS). An analysis of maritime traffic gives a better understanding of maritime operation needs and usage of natural ports, including bays within the research area. Therefore, the study focused on four sites: western approach to Horseshoe Island, Sally Cove (hosting a British station), Lystad Bay (hosting a Turkish station) and Gaul Cove. The results indicate that there has been no multiyear sea ice around Horseshoe Island. The most suitable months for the safe navigation of any type of ship in the area, due to the greatest number of ice-free days, are March, February, April and January. The study reveals that, in accordance with the Polar Code, lower ice class ships are required for safe navigation during scientific expeditions to Horseshoe Island. Also, as the average number of days with clear skies was 38, and average cloudiness very high, the use of optical satellites for long-term monitoring studies on Horseshoe Island is not recommended.